THE IMPORTANCE OF USING INTERACTIVE TECHNIQUES IN TEACHING MATHEMATICS - Mahmudova Ozoda Yuldashevna (Galaxy International Interdisciplinary Research Journal, 2024)
This article shows the effective aspects of the use of innovative methods in mathematics lessons, the state of integration between disciplines, the possibilities of information and communication technologies in the creation of innovative methods. The article also recommended techniques” advertising“,” rainbow Polish“,” double fingers“, innovatsoin” Krassvord".